Research Progress on Traditional Chinese Medicine in Alzheimer’s Disease via Intervention in Apoptosis - Zhou, Chunman; Zhang, Shiyao; Wang, Hui (Journal of Contemporary Medical Practice, 2025)
Neurodegenerative diseases (AD, PD, HD, ALS) share the common pathological endpoint of “irreversible neuronal loss,” with apoptosis serving as the “terminal common pathway” driving disease progression. Alzheimer’s disease (AD) is a chronic, progressive neurodegenerative disorder characterized primarily by the gradual deterioration of cognitive and memory functions. Its pathological hallmarks include neurofibrillary tangles formed by aggregates of hyperphosphorylated microtubule-associated protein (Tau) and amyloid plaques resulting from β-amyloid protein aggregation. The exact pathogenesis of AD remains incompletely understood, and there are currently no effective disease-modifying treatments or curative approaches available in clinical practice. In recent years, the incidence of AD has shown an increasing trend, significantly impacting public health and quality of life. Therefore, identifying effective therapeutic agents and compounds for AD is of paramount importance. Neuronal loss in Alzheimer’s disease is not merely a result of Aβ or Tau “toxic proteins” directly killing cells. Rather, it is the consequence of “programmed cellular suicide” induced by the persistent activation of apoptotic signaling networks by these agents. Modern medical research has revealed that intervening in apoptosis plays a crucial role in the pathophysiological development of AD. Furthermore, traditional Chinese medicine (TCM) has a long history of application in treating neurodegenerative diseases, offering advantages such as fewer adverse effects and the characteristic of multi-target, multi-link, and multi-pathway intervention. Consequently, based on reviewing and analyzing the latest domestic and international research, this article elaborates on the role of apoptosis in the onset and progression of AD and summarizes recent advances in TCM interventions targeting apoptotic pathways for AD treatment. The aim is to provide references and a foundation for developing clinical drugs to prevent and treat AD and to offer a broader perspective on the potential of TCM in managing this condition.